Correlation of Ki67 expression with estrogen receptor (ER) and progesterone receptor (PR) status in breast cancer - Dedy Hermansyah; Muhammad Al Anas; Kania Haura Chalisaturahmi; Mutiara Baitina; Karina Sugih Arto; Endi Taris Pasaribu (Medicinski glasnik, 2025)
Aim: To determine whether Ki67 can be predicted through its correlation with the estrogen receptor (ER) and progesterone receptor (PR), to identify breast cancer subtypes and evaluate cell proliferation level and prognosis. Methods: Patient clinical data were collected from medical records and pathology laboratory reports at Teaching Hospital, Faculty of Medicine, Universitas Sumatera Utara. Ki67 expression, as a proliferation marker, was measured and detected using immunohistochemistry (IHC). Ki67 data were categorized into two groups: <20% (low proliferation) and >20% (high proliferation). Statistical analysis was conducted by calculating the frequency distribution and percentage of receptor status and using the χ2 test. Results: The study revealed an inverse relationship between ER/PR status and Ki67 (<0.001). Low Ki67 levels were generally associated with positive ER/PR status, while high Ki67 levels showed increased frequency in ER/PR- negative cases. Conclusion: : Ki67 expression can be determined based on the frequency of ER/PR status; however, these markers have distinct roles in the management of breast cancer patients.
Keywords: Ki67; Breast Cancer; biomarker; immunohistochemistry; prognosis; receptors